1998
DOI: 10.1111/j.1748-7692.1998.tb00715.x
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUTION AND INNERVATION OF FACIAL BRISTLES AND HAIRS IN THE FLORIDA MANATEE (TRICHECHUS MANATUS LATIROSTRIS)

Abstract: The distribution and anatomy of sirenian perioral bristles (modified vibrissae) and facial hairs are of interest because of their use during feeding and tactile exploration. In the present study we have identified six fields of perioral bristles on the face of the Florida manatee (T. manatus latirostris), four (U1‐U4) on each side of the upper lips and oral cavity, and two (L1‐L2) on each side of the lower lip pad, inside the oral cavity and rostral to the horny mandibular pad. Each field has a characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 21 publications
3
94
1
Order By: Relevance
“…The total number of bearded seal mystacial F-SCs is similar to the number of perioral bristles in Florida manatees (Reep et al, 1998). However, all hairs on manatees are vibrissal F-SCs and the facial region possesses approximately 2,000 F-SCs (Reep et al, 1998).…”
Section: Bearded Seal F-sc Innervationmentioning
confidence: 72%
See 1 more Smart Citation
“…The total number of bearded seal mystacial F-SCs is similar to the number of perioral bristles in Florida manatees (Reep et al, 1998). However, all hairs on manatees are vibrissal F-SCs and the facial region possesses approximately 2,000 F-SCs (Reep et al, 1998).…”
Section: Bearded Seal F-sc Innervationmentioning
confidence: 72%
“…However, all hairs on manatees are vibrissal F-SCs and the facial region possesses approximately 2,000 F-SCs (Reep et al, 1998). In spite of the large number of manatee F-SCs, the mean number of myelinated axons innervating just the mystacial vibrissal array of bearded seals is 2.9 times greater than in the entire facial region of Florida manatees (Reep et al, 2001).…”
Section: Bearded Seal F-sc Innervationmentioning
confidence: 97%
“…As with pinnipeds, sirenians have sensitive vibrissae that help these animals navigate the environment, with the aid of color vision (Griebel and Schmidt, 1996;Newman and Robinson, 2006). The West Indian manatee has over 5300 vibrissae covering its entire body; about 2000 of these vibrissae are located in the facial region (Reep et al, 1998). Manatees use their facial hairs for different functions (Bachteler and Dehnhardt, 1999) and both facial and postfacial vibrissae help the manatee detect hydrodynamic stimuli and navigate its environment (Reep et al, 2011).…”
Section: Somatosensationmentioning
confidence: 99%
“…The facial bristles and hairs are used not only for tactile exploration and discrimination Bachteler and Dehnhardt, 1999] but also for oripulatory grasping of plants during feeding 2000]. Recently, we reported that all the hairs and bristles in the facial region of the Florida manatee are modified vibrissae associated with F-SCs having substantial innervation [Reep et al, 2001]. Dosch [1915] reported that all hairs on the bodies of sirenians were sinus hairs.…”
Section: Introductionmentioning
confidence: 99%